Bridges over borders: examining the success factors and spatial dynamics of tourism-themed cross-border projects in Hungary - Czimre, Klára; Bacsa-Papp, Zsuzsanna; Țoca , Constantine-Vasile; Tătar, Corina-Florina Tătar (Acta Geographica Debrecina Landscape & Environment series, 2026)
Tourism serves as the primary engine for cross-border integration within EU Cohesion Policy, representing the most dominant thematic objective in Interreg, IPA, and ENI frameworks. Analysis of the keep.eu dataset reveals that while 247 programmes have supported over 4,700 tourism projects, the sector is intrinsically linked to cultural heritage and education as “soft-power” tools for territorial cohesion. Hungary ranks in the top decile for project participation with 440 initiatives, yet a moderate partnership-to-project ratio indicates a strategic preference for bilateral cooperation over complex multilateral networks. Spatial distribution shows significant clustering along the Serbian, Romanian, and Croatian borders, whereas regional strategic priorities in other areas often emphasize cultural heritage, education and institutional cooperation over direct tourism development. The “Route of Medieval Churches” case study validates that successful integration depends on moving beyond fragmented restoration toward “sellable” tourism products through bilingualism and digital innovation. Effective cross-border cooperation requires a five-dimensional synergy where integrated marketing and strategic branding outweigh standalone infrastructural investments. For the 2021–2027 budgetary cycle, shifting focus from physical assets to cohesive destination identity is essential for long-term sustainability and regional competitiveness.